The Triad of Paying Creditors, Collecting Debts, and Moving Inventory as Engines of Entrepreneurial Success in Nigerian Oil and Gas Firms - Gilbert Ogechukwu Nworie; Ogunmodede Olorunfemi; Uche Chukwu (PT Mattawang Mediatama Solution, 2025)
Many Nigerian oil and gas firms struggle with managing creditors, debtors, and inventory efficiently. These challenges limit cash flow, reduce profitability, and constrain growth. As a result, entrepreneurial success in these firms is often hindered by poor operational liquidity management. Hence, this study examined the effect of paying creditors, collecting debts, and managing inventory on entrepreneurial success (proxy by return on sales) in Nigerian oil and gas firms. An ex-post facto research design was adopted, covering the period from 2012 to 2024. The population consisted of eight listed oil and gas firms, with six selected for the study through purposive sampling. Secondary data were collected from the annual reports of the selected firms, and hypotheses were tested using a fixed effects panel regression model with Cross-section seemingly unrelated regression (SUR) standard errors to correct for heteroskedasticity. The findings revealed that: Days Inventory Outstanding has a negative and significant effect on entrepreneurial success (? = -0.616, p = 0.0213); Days Receivable Outstanding has a positive and significant effect on entrepreneurial success (? = 0.005534, p = 0.0000); Days Payable Outstanding has a negative but insignificant effect on entrepreneurial success (? = -0.002935, p = 0.8554). In conclusion, efficient inventory control is essential because holding excessive stock ties up capital that could support productive activities, while effective management of receivables enhances profitability by maintaining balanced credit policies and ensuring timely collections to improve cash flow and sustain operations. The study recommended that operations managers in Nigerian oil and gas firms should reduce the time inventory is held by implementing efficient inventory management systems, optimizing stock levels, and improving turnover to enhance profitability.